Gestión de residuos sólidos domésticos para la parroquia rural El Retiro, cantón Machala, El Oro - Cañar Gómez, Freddy Gérman (Machala : Universidad Técnica de Machala, 2018)
This project analyzes the Domestic Solid Waste Management of the El Retiro Rural Parish of Machala Canton by means of the problematic one that will be found to be the lack of adequate treatment of domestic solid waste, thus generating contamination, proliferation of noxious fauna, degradation of culture are produced by the emission of bad odors, transmission of diseases and visual impact in the parish, this result was obtained through a survey conducted in the area and research on the management of solid waste since its generation, collection, separation and final disposal in the Sanitary Landfill of Machala, in addition it was possible to establish a proposal for the management of the organic waste by means of the creation of a guide for the reuse of solid domestic waste by means of the elaboration of organic fertilizer specifically the denominated compost, this will be of great benefit for the inhabitants of the zone and its plantations.
En este proyecto se analiza la Gestión de Residuos Sólidos Domésticos de la Parroquia Rural El Retiro del Cantón Machala mediante la problemática encontrada que es la falta de tratamiento adecuado de los residuos sólidos domésticos generando así contaminación, proliferación de fauna nociva, degradación de la cultura estos son producidos por la emisión de malos olores, transmisión de enfermedades e impacto visual en la parroquia, este resultado se obtuvo mediante una encuesta realizada en la zona e investigación del manejo que tienen los residuos sólidos desde su generación, recolección , separación y disposición final en el Relleno Sanitario de Machala, además se logró establecer una propuesta para el manejo de los desechos orgánicos mediante la creación de una guía para las reutilización de residuos sólidos domésticos mediante la elaboración de abono orgánico específicamente el denominado compost, esto será de gran beneficio para los habitantes de la zona y sus plantaciones.
Keywords: RESIDUOS; DESECHOS; RELLENO SANITARIO; COMPOST